The last voyage of Poe Blythe - Condie, Allyson Braithwaite (Dutton Books, 2019)
Seeking to avenge the murder of her true love while on a dredge ship searching for gold, fifteen-year-old captain Poe Blythe becomes the architect of new defenses designed to destroy her enemies.